2018
DOI: 10.1111/jth.14007
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant bleeding in cancer patients treated for venous thromboembolism from the CATCH study

Abstract: Background Cancer patients with acute venous thromboembolism (VTE) receiving anticoagulant treatment have an increased bleeding risk. Objectives We performed a prespecified secondary analysis of the randomized, open-label, Phase III CATCH trial (NCT01130025) to assess the rate and sites of and the risk factors for clinically relevant bleeding (CRB). Patients/Methods Patients with active cancer and acute, symptomatic VTE received either tinzaparin 175 IU kg once daily or warfarin (target International Normalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 35 publications
0
17
0
4
Order By: Relevance
“…There is a gap in knowledge of predictive variables for MB in active cancer patients that was addressed by the RIETE group’s bleed risk stratification of the general population which included all cancer (OR = 1.7, 95%CI: 1.4-2.2) among others clinical risk items, receiving LMWH plus VKA[42]. Kamphuisen et al[43] on behalf of the CATCH trial presented the first pre-specified second analysis were a metastatic stage, older age (> 75 years old) and intracranial lesions described on clinical risk considerations in CAVTE with LMWH (tinzaparin) for major bleed. We found that active systemic treatment and active smoker significantly contributed to treatment failure, regardless of the therapy modality or packs per year smoked, respectively (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…There is a gap in knowledge of predictive variables for MB in active cancer patients that was addressed by the RIETE group’s bleed risk stratification of the general population which included all cancer (OR = 1.7, 95%CI: 1.4-2.2) among others clinical risk items, receiving LMWH plus VKA[42]. Kamphuisen et al[43] on behalf of the CATCH trial presented the first pre-specified second analysis were a metastatic stage, older age (> 75 years old) and intracranial lesions described on clinical risk considerations in CAVTE with LMWH (tinzaparin) for major bleed. We found that active systemic treatment and active smoker significantly contributed to treatment failure, regardless of the therapy modality or packs per year smoked, respectively (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with the risk of bleeding include thrombocytopenia caused by chemotherapy [22] while age >75 was identified as significant risk factor of CRB (RR 1.79 (95% CI 1.18–2.70) p = 0.013) [23].…”
Section: Risk Of Thrombosis and Bleeding In Patients With Cancermentioning
confidence: 99%
“…In the secondary analysis of the CATCH trial, there was a 15.3% incidence rate of clinically relevant bleeding in patients treated with either LMWH or warfarin over a 6month period. 34 In comparison to LMWH, DOACs have shown a similar rate of bleeding in a large, retrospective analysis (13 vs. 11%; p ¼ 0.746). 35 The anticoagulation management of GI-cancer associated VTE is even more challenging when patients are thrombocytopenic, which is relatively common when patients are treated with chemotherapy.…”
Section: Management Anticoagulationmentioning
confidence: 96%